Analisis Faktor-faktor yang Berhubungan dengan Persepsi Tenaga Kesehatan terhadap Penerapan Budaya Keselamatan Pasien di RSUP Prof. Dr. R. D. Kandou Manado - Neni Ekawardani; Aaltje E. Manampiring; Erwin G. Kristanto (Universitas Sam Ratulangi, 2022)
Abstract: Patient safety is a joint commitment regarding patient safety from each individual or group to create a safe service environment. This study aimed to determine the factors related to the perception of health workers on the application of patient safety culture at Prof. Dr. R. D. Kandou Hospital, Manado. This was an analytical and descriptive study with a cross sectional design. Sampling used non-probability sampling technique in consecutive sampling. We used a questionnaire that had been tested for validity and reliability. Data were analyzed univariate, bivariate using the Spearman Rank test, and multivariate using the logistic regression test with the SPSS program. There were 324 respondents in this study. The statistical analysis showed that the teamwork in work units and management support for perceptions of patient safety culture implementation had a significant value with a very strong correlation (r=0.803; r=0.897). Commu-nication, collaboration between works units, and the frequency of reporting incidents on the perception of implementing safety culture in patients also has significant value with a strong correlation (r=0.706; r=0.671; r=0.624). Management support was the most dominant variable with odds ratio value of 125.244. In conclusion, there was a strong to very strong positive relationship in the factors of teamwork in work units, communication, cooperation between work units, incident reporting frequency, and management support related to the perception of health workers toward the application of a patient safety culture at Prof. Dr. R. D. Kandou Hospital, Manado. Keywords: perceptions of health workers; patient safety culture; hospital Abstrak: Budaya keselamatan pasien merupakan komitmen bersama terkait keselamatan pasien dari setiap individu atau kelompok untuk menciptakan lingkungan pelayanan yang aman. Tujuan penelitian untuk mengetahui faktor-faktor yang berhubungan dengan persepsi tenaga kesehatan terhadap penerapan budaya keselamatan pasien di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian deskriptif analitik dengan desain potong lintang. Penentuan sampel dengan teknik non probability sampling secara consecutive sampling. Kami menggunakan kuesioner yang telah teruji validitas dan reliabilitasnya. Data dianalisis menggunakan program SPSS secara univariat, bivariat menggunakan uji Spearman Rank, dan multivariat menggunakan uji regresi logistik. Hasil penelitian mendapatkan 324 responden. Uji statistik menunjukkan hubungan kerjasama tim di unit kerja dan dukungan manajemen terhadap persepsi penerapan budaya keselamatan pasien yang bermakna dengan nilai korelasi sangat kuat (r=0,803; r=0,897). Hubungan komunikasi, kerjasama tim antar unit, dan frekuensi pelaporan insiden terhadap persepsi penerapan budaya keselamatan pasien yang bermakna dengan nilai korelasi yang kuat (r=0,706; r=0,671; r=0,624). Faktor dukungan manajemen yang paling dominan dengan nilai odds ratio 125,244. Simpulan penelitian ini ialah terdapat hubungan positif kuat hingga sangat kuat pada faktor kerjasama tim di unit kerja, komunikasi, kerjasama antar unit kerja, frekuensi pelaporan insiden, dan dukungan manajemen dengan persepsi tenaga kesehatan terhadap penerapan budaya keselamatan pasien di RSUP Prof. Dr. R. D. Kandou Manado. Kata kunci: persepsi tenaga kesehatan; budaya keselamatan pasien; rumah sakit